1996
DOI: 10.1177/000348949610500813
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Computed Tomographic Evaluation of the Cochlear Capsule in Otosclerosis: Relationship between Densitometry and Sensorineural Hearing Loss

Abstract: Otosclerotic cochlear involvement is a rather frequent disease that has not been clearly understood in terms of diagnosis and management. Objective evaluation methods are needed to confirm the clinical diagnosis, investigate the relationship with hearing impairment, and validate the results of treatment. In this study two ear groups with bone conduction hearing loss (BCHL) were investigated with audiometry and high-resolution computed tomography (HRCT). In the first group (n = 22) the diagnosis of fenestral ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
2
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 11 publications
0
43
2
3
Order By: Relevance
“…Swartz et al [19] have shown a correlation between decalcification of the otic capsule and SNHL at high, middle, and low frequencies, although quantitative evaluation, such as densitometry, was not performed. In other reports using a 1.5-mm slice thickness, it has been shown that the highest correlation is seen in the middle cochlear turn or the basal cochlear turn [18,19]. In the present study, although the highest negative correlation was observed in ROIs 2, 5, and 6, corresponding to the middle turn, no clear correlations were found between the position of decalcification and the hearing loss frequency.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Swartz et al [19] have shown a correlation between decalcification of the otic capsule and SNHL at high, middle, and low frequencies, although quantitative evaluation, such as densitometry, was not performed. In other reports using a 1.5-mm slice thickness, it has been shown that the highest correlation is seen in the middle cochlear turn or the basal cochlear turn [18,19]. In the present study, although the highest negative correlation was observed in ROIs 2, 5, and 6, corresponding to the middle turn, no clear correlations were found between the position of decalcification and the hearing loss frequency.…”
Section: Discussioncontrasting
confidence: 70%
“…Although the CT densitometry of fenestral otosclerosis and the correlation between CT densitometry and audiometry have been reported [16][17][18][19][20][21][22], there have been few reports concerning CT densitometry or the cutoff value for the diagnosis of otosclerosis using CT images with a slice thickness of 0.5 mm.…”
Section: Introductionmentioning
confidence: 99%
“…In the active phase, socalled osteospongiosis, the normal lamellar bone is resorbed and through a vascular stage is replaced by thick, irregular bone in the normal middle layer of the otic capsule [Guneri et al, 1996]. The subsequent hearing loss can be conductive, which is most commonly caused by stapes fixation due to plaque formation around the oval window, or sensorineural in the case of cochlear involvement.…”
Section: Introductionmentioning
confidence: 99%
“…This suggestion is supported by many bone disease study that has stated a relationship concerning BMD in cochlear capsule beside sensorineural auditory impairment [41,42], and previous studies about the renal system that indicated an association between decreased glomerular filtration rate and neurosensory hearing impairment [43].…”
Section: Al-khfajy Et Almentioning
confidence: 58%